Pathogen reduction technologies: The pros and cons for platelet transfusion. (2nd January 2018) - Magron, Audrey; Laugier, Jonathan; Provost, Patrick; Boilard, Eric
Abstract: The transfusion of platelets is essential for diverse pathological conditions associated with thrombocytopenia or platelet disorders. To maintain optimal platelet quality and functions, platelets are stored as platelet concentrates (PCs) at room temperature under continuous agitation—conditions that are permissive for microbial proliferation. In order to reduce these contaminants, pathogen reduction technologies (PRTs) were developed by the pharmaceutical industry and subsequently implemented by blood banks. PRTs rely on chemically induced cross-linking and inactivation of nucleic acids. These technologies were initially introduced for the treatment of plasma and, more recently, for PCs given the absence of a nucleus in platelets. Several studies verified the effectiveness of PRTs to inactivate a broad array of bacteria, viruses, and parasites. However, the safety of PRT-treated platelets has been questioned in other studies, which focused on the impact of PRTs on platelet quality and functions. In this article, we review the literature regarding PRTs, and present the advantages and disadvantages related to their application in platelet transfusion medicine.